Link Search Menu Expand Document

Arithmetic with remainders

We now have $\mathbb{Z}$ at our disposal. Conceptually, the integers are a wonderful tool. Practically, we can only even consider finitely many things.

For example, on your computer now, there is only a finite amount of memory. It is a very large collection of what can be viewed as switches. To store data, these switches can be in the on position or the off position. Suppose we have $b$ switches. Suppose we have a number $n$ that we wish to store in memory. How can we do that with switches?

A question we can ask about $n$ to help pin it down is whether it is even or odd. Since it is a binary choice, it can be captured completely using a single switch. To store this information, we just remember the value $n \mod 2$.

While knowing $0$ versus $1$ (for even vs odd) is useful, we generally want to work with larger numbers. Let $\epsilon_0$ be the remainder from dividing $m$ by $2$. Then $m \equiv \epsilon_0 \mod 2$ and $ m - \epsilon_0 = 2m_1$ for some $m_1$.

This $m_1$ itself could be even or odd. Let $\epsilon_1$ be its remainder when divided by $2$. Then \(m - \epsilon_0 - 2\epsilon_1 = 4m_2\) So \(m \equiv \epsilon_0 + 2 \epsilon_1 \mod 4\)

We can continue this process to write \(m \equiv \sum_{j = 0}^{n-1} \epsilon_j 2^j \mod 2^n\) and each $\epsilon_j \in \lbrace 0,1 \rbrace$.

Since $\equiv_m$ is an equivalence relation, we can form its quotient.

Definition. The integers mod $m$, denoted $\mathbb{Z}/m\mathbb{Z}$, are the quotient \(\mathbb{Z}/m\mathbb{Z} := \mathbb{Z}/\equiv_m\) of $\mathbb{Z}$ by the equivalence relation $\equiv_m$.

Remember that this means that \(\mathbb{Z}/m\mathbb{Z} = \lbrace [n] \mid n \in \mathbb{Z} \rbrace\) where each \([n] = \lbrace n' \mid n' \equiv n \mod m \rbrace\) are equivalence classes.

Recall that the division algorithm on $\mathbb{Z}$ takes in $n \in \mathbb{Z}$ and $m \in \mathbb{N}$ and outputs $q_n,r_n \in \mathbb{Z}$ with \(n = q_n m + r_n\) and \(0 \leq r_n < m\) Moreover, $q_n$ and $r_n$ along with $m$ uniquely determine $m$.

Lemma. Let $m \in \mathbb{N}$. The function \(\begin{aligned} r : \mathbb{Z} & \to \mathbb{N} \\ n & \mapsto r_n \end{aligned}\) descends to \(\overline{r} : \mathbb{Z}/m\mathbb{Z} \to \mathbb{N}\) Moreover, it is a bijection with its image $\lbrace n \mid 0 \leq n < m \rbrace$.

Proof. (Expand to view)

To show that a function descends to the quotient by an equivalence relation, we need to show that it is _constant_ on equivalence classes, ie whenever $n \equiv n' \mod m$ we have $r_n = r_{n'}$. By definition, we have $n - n' = cm$ for some $c$. Thus, $$ q_n m + r_n - (q_{n'}m + r_{n'}) = cm $$ or $$ r_n - r_{n'} = (c - q_{n'} + q_n)m $$ In other words, $r_n - r_{n'}$ is divisible by $m$. But since $0 \leq r_n, r_{n'} < m$, we have $$ -m < r_n - r_{n'} < m $$ The only number strictly between $-m$ and $m$ that is divisible by $m$ is $0$. So $$ r_n = r_{n'} $$ So we see that $r$ is constant on equivalence classes. Since $r_j = j$ for $0 \leq j < m$, we see that the image of $r$ is $\lbrace n \mid 0 \leq n < m \brace$. To finish, we check that $\overline{r}$ is injective. Assume that $r_n = r_{n'}$. Then $$ n - n' = q_n m + r_n - (q_{n'}m + r_n) = (q_n - q_{n'})m $$ so $n \equiv n' \mod m$. Thus, $\overline{r}$ is injective and a bijection onto its image.

Example. Let’s take $m=5$. The previous lemma says that \(\mathbb{Z}/5\mathbb{Z} = \lbrace [0], [1], [2], [3], [4] \rbrace\) We can figure out which box to place $n \in \mathbb{Z}$ into mod $5$ by determining its remainder after division by $5$. So $22 = 4\cdot 5 + 2$ and $[22] = [2]$.

We can also transport arithmetic from $\mathbb{Z}$ to $\mathbb{Z}/m\mathbb{Z}$.

Definition/Lemma. We add two elements of $\mathbb{Z}/m\mathbb{Z}$ using the rule \([n] + [n'] := [n+n']\) and we multiply via \([n] \cdot [n'] := [nn']\)

This is tagged as a lemma because rules we have written down for outputs depend, ostensibly, on the choice of representative for the equivalence class. For example, mod $5$, we have \([22] + [3] = [25]\) and \([2] + [3] = [5]\) But $[22] = [2]$ so we better have $[25] = [5]$. Indeed we do.

Proof. (Expand to view)

We need to check that if $n_1 \equiv n_2 \mod m$ and $n_1' \equiv n_2' \mod m$ then $n_1 + n_1' \equiv n_2 + n_2' \mod m$ and $n_1n_1' \equiv n_2n_2' \mod m$. Assume that $n_1 \equiv n_2 \mod m$ and $n_1' \equiv n_2' \mod m$. Then by definition $n_1 - n_2 = c_1m$ and $n_1' - n_2' = c_2 m$. Then $$ n_1 + n_1' - (n_2 + n_2') = c_1 m + c_2 m + (c_1+c_2) m $$ so indeed $n_1 + n_1' \equiv n_2 + n_2' \mod m$. Being a little more clever, we have $$ n_1 \cdot n_1' - n_2 \cdot n_2' = n_1 \cdot n_1' - n_1 \cdot n_2' + n_1 \cdot n_2' - n_1' \cdot n_2' = n_1c_2m - n_2'c_1 m= (n_1c_2 - n_2'c_1)m $$

Example. Let’s work out the multiplication table for $\mathbb{Z}/5\mathbb{Z}$. We have